2020
DOI: 10.1371/journal.pone.0242137
|View full text |Cite
|
Sign up to set email alerts
|

Soluble dimeric prion protein ligand activates Adgrg6 receptor but does not rescue early signs of demyelination in PrP-deficient mice

Abstract: The adhesion G-protein coupled receptor Adgrg6 (formerly Gpr126) is instrumental in the development, maintenance and repair of peripheral nervous system myelin. The prion protein (PrP) is a potent activator of Adgrg6 and could be used as a potential therapeutic agent in treating peripheral demyelinating and dysmyelinating diseases. We designed a dimeric Fc-fusion protein comprising the myelinotrophic domain of PrP (FT2Fc), which activated Adgrg6 in vitro and exhibited favorable pharmacokinetic properties for i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…GFAP levels in uninjured Prnp ZH3/ZH3 mice appeared higher than in WT mice. By comparing GFAP expression in uninjured Prnp ZH3/ZH3 and WT nerves ( Fig 1e ) we found that Prnp ZH3/ZH3 mice had on average a two-fold higher baseline GFAP level when compared to WT mice (relative increase to WT GFAP level as quantified from Fig 1e : WT 1.00 ± 0.17 ( 6 ); Prnp ZH3/ZH3 2.05 ± 0.09 ( 6 ); mean ± SEM ( n ); p = 0.0003, unpaired t-test), which is in line with our previously published findings [ 31 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…GFAP levels in uninjured Prnp ZH3/ZH3 mice appeared higher than in WT mice. By comparing GFAP expression in uninjured Prnp ZH3/ZH3 and WT nerves ( Fig 1e ) we found that Prnp ZH3/ZH3 mice had on average a two-fold higher baseline GFAP level when compared to WT mice (relative increase to WT GFAP level as quantified from Fig 1e : WT 1.00 ± 0.17 ( 6 ); Prnp ZH3/ZH3 2.05 ± 0.09 ( 6 ); mean ± SEM ( n ); p = 0.0003, unpaired t-test), which is in line with our previously published findings [ 31 ].…”
Section: Resultssupporting
confidence: 91%
“…We have previously described that Prnp ZH3/ZH3 mice exhibit an early upregulation of repair Schwann cell markers in sciatic nerves, which probably represents an early sign of the peripheral nerve disease [ 31 ]. In the present study, we confirmed that the 2–3 months old Prnp ZH3/ZH3 mice undergoing crush injury showed a two-fold upregulation of GFAP in their uninjured sciatic nerves when compared to WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, no changes in the expression of neuron-enriched transcript were detectable at this time point. Instead, suppression of neuronal transcripts was only observed at the terminal stage of disease (Sorce et al, 2020). The onset of changes associated with actively translating genes during the course of prion infection also revealed glial perturbation as the major contributors in driving the course of prion disease (Scheckel et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have longitudinally mapped transcriptional changes associated with prion disease in mice, and revealed changes in gene expression from as early as 4 weeks post prion infection (Sorce et al, 2020). We asked if GFAP Cre ;loxPrP mice, which do not develop clinical signs after prion infection, exhibit transcriptional changes upon prion infection.…”
Section: Prion Infection Does Not Elicit Its Transcriptional Signaturmentioning
confidence: 99%
See 1 more Smart Citation